Structuration of a definition of Natural Ingredients prototype - Ramírez-Navas, Juan Sebastián; Rojas-Renjifo, Katerine; Cardenas-Nieto, José David; Sánchez Mejía, Myriam (Revista Colombiana de Investigaciones Agroindustriales, 2020)
The structuring of definitions is one of the essential components of the process of creation and development of knowledge. The concept of a prototype is designed to explore, approve, or validate different aspects of the product and, finally, demonstrate compliance with the objectives of the proposed design and the requirements of the identified market. In the project: “Fortalecimiento de las capacidades de investigación, desarrollo e innovación (I+D+i) para la producción de ingredientes naturales (IN) a partir de biomasa residual (BR), Palmira, Valle del Cauca, Occidente-IN SGR CTI”, one of the aims was to obtain three prototypes of natural ingredients (PNI) from residual agricultural and agro-industrial biomass of tropical fruit trees locally produced, differentiating, and innovative of world-class. For this project, two workshops were held: a theoretical-practical one to define PNI and establish its scope and an internal one, to analyze the results. The first workshop had two stages: the first one (lectures) and the second one (teamwork to generate PNI definitions). In the second workshop, the definitions were analyzed and consolidated. As a result, it was concluded that this definition should consider the following elements: production at scale, functions of the prototype (exploration, approval, and validation), and demonstrations of compliance with the design objectives (acceptability and market requirements).